Selective Inhibition of Protease-activated Receptor 4-dependent Platelet Activation by YD-3 - Wu, Chin-Chung; Hwang, Tsong-Long; Liao, Chang-Hui; Kuo, Sheng-Chu; Lee, Fang-Yu; Lee, Chun-Yann; Teng, Che-Ming (Thrombosis and Haemostasis, 2002)
In the present study, the antiplatelet effect and its mechanism of a new synthetic compound YD-3 [1-benzyl-3-(ethoxycarbonylphenyl)-indazole] were examined. YD-3 inhibited the aggregation of washed human platelets caused by protease-activated receptor (PAR) 4 agonist peptide GYPGKF (IC50 = 0.13 ± 0.02 µM), but had no or little effect on that by thrombin, PAR1 agonist peptide SFLLRN, collagen or U46619. YD-3 produced a parallel, rightward shift of the concentration-response curve for GYPGKF without decreasing of the maximum platelet aggregation, indicating a competitive antagonism. In contrast to human platelets, both thrombin- and GYPGKF-induced mouse platelet shape change and aggregation were completely inhibited by YD-3. YD-3 also selectively prevented GYPGKF-induced intracellular Ca2+ mobilization in human platelets. Furthermore, in the PAR1-desensitized human platelets, thrombin induced a relatively slow rise and decay of calcium mobilization that was significantly inhibited by YD-3. In addition, the synergistic effect of SFLLRN and GYPGKF on platelet activation was prevented by YD-3. YD-3 also inhibits both fMLP-stimulated neutrophil- and purified cathepsin G-induced platelet aggregation, which has been demonstrated to be PAR4-dependent. Taken together, our results suggest that YD-3 selectively inhibits PAR4-dependent platelet activation through blockade of PAR4. To the best of our knowledge, it is the first non-peptide PAR4 antagonist.
Keywords: Protease-activated receptor; platelet activation; YD-3